Implementation of Murabahah Agreement Based on PSAK 102 from a Maslahah Perspective at Bank Muamalat - Nurfadillah Annisa Arifin; Sumarlin; Raodatul Jannah (Indonesian Journal of Taxation and Accounting, 2025)
Study this analysis implementation contract murābahah on mortgage financing at Bank Muamalat Gowa Branch based on PSAK 102 and the concept maslahah . The focus of the study includes the contract mechanism, accounting records with PSAK 102, and its contribution to the public welfare. The study uses a qualitative descriptive approach with data from interviews, internal documents, and related literature. The results show that the implementation of murābahah is generally in accordance with sharia principles, although compliance with PSAK 102 has not been fully achieved, especially in the recognition margin, disclosure of additional costs, and the use of wakalah. From a maslahah perspective, this financing provides real benefits through fair and transparent access to home ownership. Maintaining aspects of fairness and transparency is necessary for these benefits to be optimal. This study contributes to the development of sharia accounting and serves as a practical reference for sharia banks and regulators in improving transparency, accountability, and compliance with sharia principles.